Pengaruh Desain Interior Museum Geologi Bandung terhadap Pengalaman Ruang Pengunjung dalam Mencapai Keterlibatan Emosional: - Zakiah, Kiki; Santosa, Imam (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
This study explores the impact of museum interior design on visitors' spatial experiences in achieving emotional engagement, focusing on The Life History Exhibition Room at the Bandung Geological Museum. This exhibition room showcases geological collections and prehistoric animal fossils. Located in a heritage building, it offers a unique experience that combines history with elements of colonial architecture. The research is grounded in Mary Jo Bitner’s Servicescape theory and the emotional design theory by Donald Norman, emphasizing the importance of physical space elements in shaping visitors' experiences and fostering emotional engagement, which is crucial for enhancing their understanding of museum information. The study employs a qualitative method with a case study approach, including literature reviews, observations, in-depth interviews with visitors, museum managers, interior designers, and heritage experts. Data was also collected through an initial questionnaire to identify visitor’s perceptions and preferences regarding their favorite exhibition spaces in the museum. The findings indicate that interior design elements such as lighting, layout, and artifacts significantly impact visitor’s emotional responses—visceral, behavioral, and reflective. The replica of a dinosaur fossil, as the museum's iconic feature, generates strong initial attraction, while the exhibition's narrative fosters deep reflection on the history of life on Earth. This research recommends a holistic interior design strategy for museums to create meaningful experiences for Generation Z while helping museum managers enhance emotional engagement and cultural appreciation through exhibition interior design.